Intrusive Imagery in Psychopathology: A Commentary - Moulds, M; Holmes, E (2011)
Spontaneous, intrusive images of negative events are commonly experienced in everyday life. In clinical disorders, this imagery is extreme: recurrently experienced, highly distressing and vivid, and capable of eliciting significant negative affect. This special issue under the editorial lead of Julie Krans presents an intriguing series of studies that examine the role of intrusive imagery in psychopathology. The authors of this work have applied rigorous laboratory approaches in order to address prevailing questions about the role of intrusive phenomena in clinical conditions. The studies highlight the value of convergent evidence from the laboratory and the clinic in forwarding our understanding of this topic. Furthermore, collectively, the studies speak to three key questions: (1) Must an event be experienced in order to be intrusive? (2) Do trait variables influence vulnerability to intrusion development? (3) Do encoding processes influence intrusion development? In this commentary, we reflect on the findings reported and consider them in the context of these broader themes. We discuss the ways in which the findings have scope to extend existing theoretical accounts and to inform treatment developments for disorders that are characterized by recurrent and distressing intrusions. © 2011 International Association for Cognitive Psychotherapy.